Association between LEKR1‐CCNL1 and IGSF21‐KLHDC7A gene polymorphisms and diabetic retinopathy of type 2 diabetes mellitus in the Chinese Han population. (October 2016) - Lin, Xiaohui; Wang, Jihong; Yun, Lixia; Jiang, Shuhong; Li, Langen; Chen, Xiaohai; Li, Zhen; Lu, Qiang; Zhang, Yihui; Ma, Xiaocheng
Abstract: Background: Diabetic retinopathy (DR) is one of the most common microvascular complications of diabetes. The present study aimed to identify a possible connection between gene polymorphisms and the risk of developing DR. Materials and methods: A total of 319 patients with type 2 diabetes mellitus (T2DM) were selected. All patients underwent a complete eye examination. Based on this, the patients with T2DM were divided into two subgroups: 175 patients with retinopathy (DR) and 144 patients without retinopathy (NDR). We calculated the genotype frequencies of case and control subjects using the chi‐squares test. The odds ratio (OR) and 95% confidence intervals (CIs) were calculated by unconditional logistic regression adjusted for age and sex. Results: The finding by analysis is that the mean of duration of diabetes, total cholesterol (TC), triglycerides (TG), low‐density lipoprotein (LDL), glomerular filtration rate and C‐peptide were significantly different between DR and NDR. We found significant differences in cystatin‐C concentrations with LEKR1‐CCNL1 rs13064954 and NOS3 rs3918227 of different genotypes. Significant differences in serum TG levels were seen among the three genotypes of MTHFR rs1537516. Subjects carried the T allele of IGSF21‐KLHDC7A rs3007729 had higher serum LDL concentrations ( p  = 0.015). In the allele model, LEKR1‐CCNL1 rs13064954 decreased the risk of DR (OR =0.57, 95% CI = 0.34–0.96, p  = 0.032). Under the dominant model, the IGSF21‐KLHDC7A rs3007729 CT‐TT genotype increased the risk of DR (OR =1.84, 95% CI = 1.14–2.99, p  = 0.013). Conclusions: Our results suggest that LEKR1‐CCNL1 and IGSF21‐KLHDC7A influence the development of DR.